TEACHERS’ PEDAGOGICAL KNOWLEDGE OF LEARNERS IN SENIOR HIGH SCHOOL (RETAIN, 2017)
TEACHERS’ PEDAGOGICAL KNOWLEDGE OF LEARNERS IN SENIOR HIGH SCHOOL Moch Reza Pahlevi English Education Study Program, English Language and Literature Department, Faculty of Languages and Arts, State University of Surabaya Email: mochpahlevi@mhs.unesa.ac.id Susanto English Education Study Program, English Language and Literature Department, Faculty of Languages and Arts, State University of Surabaya Email: Susantoniki@gmail.com Abstract The purpose of this study was to seek and describe teacher’s understanding in the learners’ characteristics. This study was considered as a basic interpretive research which used qualitative approach to support the choice of the source of the data. The subjects of this research were the five English teachers in senior high school. The unstructured/ in-depth of interview was applied to collect the data. Then the data obtained was analyzed and explained specifically based on researcher’s interpretation in the form of narrative and descriptive. The findings have shown four conclusions which draw the subjects’ understanding in the knowledge of learners. The subjects have a rich understanding on students’ social and cultural background, a good understanding in students’ needs, a fair understanding in students’ learning style, and a slight understanding in students’ cognitive characteristics Keywords: Teacher, Knowledge, Learners, Characteristics Abstrak Tujuan dari penelitian ini adalah untuk mencari dan menjelaskan pemahaman guru dalam karakteristik siswa. Bentuk penelitian ini adalah basic interpretive yang menggunakan pendekatan kualitatif untuk mendukung pilihan sumber data. Subyek penelitian ini adalah lima guru bahasa Inggris di SMA. Wawancara yang mendalam diaplikasikan untuk pengumpulan data. Kemudian data yang diperoleh dianalisis dan dijelaskan secara spesifik berdasarkan interpretasi peneliti dalam bentuk narasi dan deskriptif. Hasil dari penelitian ini telah menunjukkan empat kesimpulan yang menggambarkan pemahaman subyek dalam pengetahuan siswa. Subyek memiliki pemahaman yang kaya pada latar belakang sosial dan budaya siswa, pemahaman yang baik pada kebutuhan belajar siswa, pemahaman adil dalam gaya belajar siswa, dan pemahaman yang sedikit dalam karakteristik kognitif siswa. . Kata Kunci: Guru, Pemahaman, Siswa, Karakteristik